2012
DOI: 10.1097/mnm.0b013e3283561881
|View full text |Cite
|
Sign up to set email alerts
|

Increasing importance of 18F-FDG PET in the diagnosis of neurolymphomatosis

Abstract: Neurolymphomatosis (NL) is a rare clinical entity that is defined as infiltration of the nervous system by a known or unknown haematological malignancy and is difficult to diagnose. Fluorine-18 fluorodeoxyglucose (18F-FDG) PET imaging is increasingly being used in haematological malignancies. This article focus on the role of 18F-FDG PET in the diagnosis and management of NL by presenting a review of cases described in the literature. Reports on NL that used PET with or without computed tomography (CT) as a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 44 publications
1
30
0
1
Order By: Relevance
“…Interestingly, FDG-PET appears to be a highly sensitive diagnostic method for identifying NL, with a positivity rate as high as 87.5-91% (5, 6). Intense FDG uptake in the involved nerve, as observed in this case, is a typical sign of NL according to a previous report (6). Because the use of FDG-PET is recommended for staging studies and response assessments (7), more cases of NL are likely to be identified.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, FDG-PET appears to be a highly sensitive diagnostic method for identifying NL, with a positivity rate as high as 87.5-91% (5, 6). Intense FDG uptake in the involved nerve, as observed in this case, is a typical sign of NL according to a previous report (6). Because the use of FDG-PET is recommended for staging studies and response assessments (7), more cases of NL are likely to be identified.…”
Section: Discussionmentioning
confidence: 71%
“…Unlike a retrospective review of neurolymphomatosis with neurologic manifestations of LMD, in which 91% of patients showed abnormal 18 F-FDG avidity in the central or peripheral nervous system, our study demonstrates an overall lower sensitivity of 29% (LMD was detected in six of 21 cases). [17] The lower sensitivity in our study could be attributed to our focusing exclusively on spinal LMD and the fact that the patients we included were undergoing treatment at the time of their initial assessment for LMD. Additionally, our study only included patients with leptomeningeal disease confirmed by cytology.…”
Section: Discussionmentioning
confidence: 77%
“…FDG-PET is a useful adjunct to the diagnosis and is most sensitive and specific tool currently available for diagnosis of NL [4]- [7]. It may be positive even when all other modalities fail to yield the diagnosis as was in our case [5]. Tissue diagnosis remains the gold standard and there is tumor cell infiltration of endoneurium and perineurium.…”
Section: Discussionmentioning
confidence: 95%